2007
DOI: 10.1037/0882-7974.22.3.420
|View full text |Cite
|
Sign up to set email alerts
|

Task control and cognitive abilities of self and spouse in collaboration in middle-aged and older couples.

Abstract: Collaborative problem solving may be used by older couples to optimize cognitive functioning, with some suggestion that older couples exhibit greater collaborative expertise. The study explored age differences in 2 aspects of collaborative expertise: spouses' knowledge of their own and their spouse's cognitive abilities and the ability to fit task control to these cognitive abilities. The participants were 300 middle-aged and older couples who completed a hypothetical errand task. The interactions were coded f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 36 publications
(55 reference statements)
2
22
0
Order By: Relevance
“…Study 2 showed that older married spouses' levels of story recall were similar to those of younger married spouses. This result indirectly supported the notion that, with interactive experience, collaborators might coordinate their joint cognitive efforts, enhancing their performance and avoiding some inhibiting effects (Berg et al, 2007; Engeström, 1992; Garrod & Pickering, 2004; Gould, Kurzman, & Dixon, 1994; Johansson et al, 2000; Wegner, Giuliano, & Hertel, 1985). However, other research with young adult friends (Andersson & Rönnberg, 1995) and older couples (Gould et al, 2002) has produced inconsistent results.…”
supporting
confidence: 61%
See 3 more Smart Citations
“…Study 2 showed that older married spouses' levels of story recall were similar to those of younger married spouses. This result indirectly supported the notion that, with interactive experience, collaborators might coordinate their joint cognitive efforts, enhancing their performance and avoiding some inhibiting effects (Berg et al, 2007; Engeström, 1992; Garrod & Pickering, 2004; Gould, Kurzman, & Dixon, 1994; Johansson et al, 2000; Wegner, Giuliano, & Hertel, 1985). However, other research with young adult friends (Andersson & Rönnberg, 1995) and older couples (Gould et al, 2002) has produced inconsistent results.…”
supporting
confidence: 61%
“…Future research should examine the potential mnemonic function of positive but ancillary elaborative statements. Conceivably, contextualizing the story with reasonable and interesting inferences could be based on common experience (Berg et al, 2007) and serve a motivational or strategic purpose during joint recall episodes (Gould et al, 1994). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, assessment of perceptions of spouse dominance and actual controlling behavior could further clarify age differences during disagreement. Collaboration also involves directiveness and asserting control (i.e., dominance) as well as cooperation (i.e., submission) (Berg et al, 2007), underscoring the relevance of the IPC for this marital context.…”
Section: Interpersonal Theory As An Integrative Frameworkmentioning
confidence: 99%